Development of a training programme for professional nurses in South Africa – An educational response to the COVID‐19 pandemic. Issue 1 (17th June 2022) - Jordan, Portia; Iwu‐Jaja, Chinwe; Mokoka, Elizabeth; Kearns, Irene; Oamen, Benedict; de Lange, Santel; Schutte, Loraine; Naidoo, Vasanthrie
Abstract: Aim: This paper describes the development of the training programme for South African professional nurses on how to manage critically ill COVID‐19 patients in intensive care units and repurposed general wards. Design and methods: The Analysis, Design, Development, Implementation and Evaluation educational instructional design model guided the development of the training programme. A case‐based study approach and blended learning were used to deliver the six modules. Results: The training programme was developed, reviewed and validated by the coordinating team of facilitators involved in the initiative. Implementation of the training programme and the result thereof will not be discussed as part of this manuscript. Conclusion: The training programme aimed to enhance the knowledge of professional nurses in the management of critically ill patients with COVID‐19. As the pandemic evolves, a need for training and ongoing support was identified, which might address the need for surge capacity and hospital readiness planning.